Complete blood count, Vitamin D, Vitamin B12, Hepatitis A and Hepatitis B screening results in students of faculty of dentistry (Annals of Medical Research, 2021)
Aim: To evaluate the blood tests of the students of faculty of dentistry, to complete their vaccination and to start their treatment if necessary depending on the vitamin levels and complete whole blood count. Material and Methods: The study was conducted between December 2017 and March 2018 in Inönü University Faculty of Dentistry. Three tubes of venous blood sample were collected from all of the students for the tests. The data were analyzed by using SPSS ver. 22.0 software. A value of p 0.05 was considered statistically significant in all tests.Results: A total of 283 students, 160 (56.5%) female and 123 (43.5%) male, were included in the study. The mean age was 21.7 years. Anemia was detected in 46 (16.2%) of the students. Only 13 (4.59%) students had no HBV immunity and 117 (41.3%) had no immunity against Hepatitis A. Vitamin B12 deficiency was detected in only 20 (7.06%) students, while vitamin D deficiency was detected in 206 (72.79%) students.Conclusion: Most of the students had vitamin D deficiency and a large number of them were unimmunized against hepatitis A. In order the students to be able to be successful in the pre-service education and to protect both themselves and their patients from infectious diseases, we should check the vitamins and anemia levels, immunity against hepatitis and complete the deficiencies.
Keywords: Dental student; immunization; laboratory tests